AI-Enhanced Storytelling: Integrating Visual, Textual, and Auditory Elements Through Multimodality - Pratomo, Evan Raditya (Universitas Multimedia Nusantara, 2024)
This study explores the integration of Artificial Intelligence (AI) in experience design, focusing on its role in creating a multi-sensory experience that bridges visual, textual, and auditory elements. The research centers on the album